2014
DOI: 10.1021/bi5000838
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between AcrB Trimer Association Affinity and Efflux Activity

Abstract: The majority of membrane proteins function as oligomers. However, it remains largely unclear how the oligomer stability of protein complexes correlates with their function. Understanding the relationship between oligomer stability and activity is essential to protein research and to virtually all cellular processes that depend on the function of protein complexes. Proteins make lasting or transient interactions as they perform their functions. Obligate oligomeric proteins exist and function exclusively at a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Between the protomers, there is a small contact interface located between TM1 and TM8. 329 The TMDs of the protomers encircle a lipid filled central cavity 279 , 330 ( Figure 5 D). The extensive periplasmic part with a maximum diameter of 100 Å is formed by the periplasmic loops protruding into the periplasm between TM1 and TM2 as well as TM7 and TM8 ( Figure 5 A).…”
Section: Classes Of Transporter Proteinsmentioning
confidence: 99%
“…Between the protomers, there is a small contact interface located between TM1 and TM8. 329 The TMDs of the protomers encircle a lipid filled central cavity 279 , 330 ( Figure 5 D). The extensive periplasmic part with a maximum diameter of 100 Å is formed by the periplasmic loops protruding into the periplasm between TM1 and TM2 as well as TM7 and TM8 ( Figure 5 A).…”
Section: Classes Of Transporter Proteinsmentioning
confidence: 99%
“…Oligomers seem to be ~4–7 times more stable than individual monomers, with unfolding free energies of ~16–30 kcal/mol (Otzen, 2003; Curnow & Booth, 2007; Barrera et al , 2008; Veerappan et al , 2011). Oligomerization may also be necessary to achieve the full, functional fold (Valiyaveetil et al , 2002; Veerappan et al , 2011; Ye et al , 2014b). The ability to quickly assume a stable, proper fold may avoid aggregation, as all optimal interaction surfaces simultaneously converge together.…”
Section: Introductionmentioning
confidence: 99%
“…Many membrane proteins function as oligomers (Meng et al , 2009; Clarke & Gulbis, 2012; Reading et al , 2015), with some exhibiting multiple multimeric states (Kahraman & Haselwandter, 2016; Henrich et al , 2017). Further, mutations that disrupt oligomerization, perhaps even without changing monomeric structure, can cause disease (Ng et al , 2012; Ye et al , 2014b). It is thus important to understand how membrane proteins associate into complexes.…”
Section: Introductionmentioning
confidence: 99%
“…AcrB is known to function as an asymmetric homotrimer in which three AcrB subunits come together to expel antibiotic substrates through a functional rotation mechanism, where each subunit alternates among three separate conformations . Mutagenesis studies have previously identified an integral helix–helix interaction situated within the inner membrane region of the AcrB trimer . While the exact helix binding motif was not elucidated, this interaction is formed between transmembrane helix 1 (TM1) of one subunit and TM8 of a neighboring subunit (Figure ).…”
mentioning
confidence: 99%
“…While the exact helix binding motif was not elucidated, this interaction is formed between transmembrane helix 1 (TM1) of one subunit and TM8 of a neighboring subunit (Figure ). A triple mutant of AcrB’s TM8 was shown to disrupt oligomerization and subsequently efflux activity …”
mentioning
confidence: 99%